The Role Of Management Processes Reengineering In Improvement A Competitive Advantage- A Field Study On Islamic Banks Branches In The Syrian Coast - شيخ ديب, صلاح; ناطور, أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of this Search is to study the role management processes reengineering in improvement a competitive advantage for Islamic Banks , by studying management processes reengineering with its different dimensions (organizational dimension, Technological dimension, human dimension), and a competitive advantage with its different dimensions (improving the quality of services, quick response to customer needs and desires, achieving superior efficiency, achieving creativity and innovation). To achieve this, a descriptive analytical approach was adopted in the practical in the search. A questionnaire was designed and distributed on workers at Islamic Banks in the Syrian Coast . (100) members valid to analysis, The SPSS 19 program was adopted. The study concluded a set of results: there are significant relationships between management processes reengineering and improving the quality of services as a dimension of competitive advantage on Islamic Banks in the Syrian Coast. there are significant relationships between management processes reengineering and quick response to customer needs and desires as a dimension of competitive advantage on Islamic Banks in the Syrian Coast. there are significant relationships between management processes reengineering and achieving superior efficiency as a dimension of competitive advantage on Islamic Banks in the Syrian Coast. there are significant relationships between management processes reengineering and achieving creativity and innovation as a dimension of competitive advantage on Islamic Banks in the Syrian Coast. there are significant relationships between management processes reengineering and improvement a competitive advantage on Islamic Banks in the Syrian Coast.